2020
DOI: 10.1108/f-08-2019-0091
|View full text |Cite
|
Sign up to set email alerts
|

4D BIM models for smart utility relocation management in urban infrastructure projects

Abstract: Purpose The relocation of existing underground utilities in urban environments is complex because of the existence of multiple utility agencies being responsible for numerous utilities and over constrained space and time to execute maintenance works. Unfamiliar location and insufficient records of maintenance data hamper the flow of work, causing unnecessary delays and conflicts. The aim of the paper is to explore 4 dimensional Building Information Modeling as a smart solution for the management of multiple ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Where this was applied, it was reported that, utilising the 4D BIM model as a point of reference, clashes and conflicts that were not immediately perceptible to the main contractor or through 2D drawings alone were quickly highlighted. This is similar to findings reported in Vilventhan et al [63] that 4D BIM is very effective in the identification and resolution of clashes in projects. Furthermore, these sessions allowed trade contractors an opportunity to aid in the process of identifying and agreeing solutions to these issues alongside the same fellow trade contractors that they were interfacing with on site.…”
Section: Increase Collaboration With Trade Contractorssupporting
confidence: 92%
“…Where this was applied, it was reported that, utilising the 4D BIM model as a point of reference, clashes and conflicts that were not immediately perceptible to the main contractor or through 2D drawings alone were quickly highlighted. This is similar to findings reported in Vilventhan et al [63] that 4D BIM is very effective in the identification and resolution of clashes in projects. Furthermore, these sessions allowed trade contractors an opportunity to aid in the process of identifying and agreeing solutions to these issues alongside the same fellow trade contractors that they were interfacing with on site.…”
Section: Increase Collaboration With Trade Contractorssupporting
confidence: 92%
“…One remote construction project architectural firm used BIM to collaborate with the main contractor and other personnel on site, which resulted in increased and very effective collaboration in comparison to prior remote projects [56]. Furthermore, one utility relocation project BIM 3D visualization enabled clash detection and coordination of designers and various utility stakeholders [57], and an in metro-rail project 3D visualization was successfully used to persuade external stakeholders to support the project's goals [25]. A BIM 4D simulation enabled the tracking of actual progress of relocation works and thus improved coordination in the construction phase [57].…”
Section: Regular Bim Used For Integration and Collaboration Of Construction Stakeholdersmentioning
confidence: 99%
“…Furthermore, one utility relocation project BIM 3D visualization enabled clash detection and coordination of designers and various utility stakeholders [57], and an in metro-rail project 3D visualization was successfully used to persuade external stakeholders to support the project's goals [25]. A BIM 4D simulation enabled the tracking of actual progress of relocation works and thus improved coordination in the construction phase [57]. In many cases of BIM usage, the benefit of better coordination is reported, and Maskil Leitan and Reychav [58] conclude that BIM leads to the formation of a new and possibly much more cooperative organizational infrastructure in which conducting proper stakeholder management can greatly contribute to project success.…”
Section: Regular Bim Used For Integration and Collaboration Of Construction Stakeholdersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the network-related BIM complexity research articles investigated the complex evolution or dynamics issues of BIM in different contexts. Specifically, as mentioned earlier, BIM implementation has evolved and spread to architectural heritage maintenance projects [39] and utility relocation projects [40], which involve quite different and complex networks of stakeholders. Moreover, the range and contingencies of causal structures shaping the evolution of BIM-based operations were studied.…”
Section: Qualitative Evaluationmentioning
confidence: 99%